2022
DOI: 10.4103/jehp.jehp_1248_21
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being and coping strategies among secondary school teachers

Abstract: INTRODUCTION: Educators, academicians, and teachers are responsible for the development of the nation's human capital. Teacher coping methods are becoming more widely recognized as a key factor in determining teacher effectiveness. The aim of this study was to identify the various coping strategies adopted by high school teachers in Southern India. MATERIALS AND METHODS: A cross-sectional study was conducted in government, aided, and unaided schools of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
3
6
0
1
Order By: Relevance
“…Moreover, no one mentioned negative coping strategies. Although this may be due to social desirability bias, previous research has suggested that most teachers usually adopt positive rather than negative coping strategies in their professional life [54,55], again, especially if their levels of stress are low or moderate [36,56]. Future research may investigate coping strategies more deeply and monitor them over time to understand if and how they change in parallel with stress levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no one mentioned negative coping strategies. Although this may be due to social desirability bias, previous research has suggested that most teachers usually adopt positive rather than negative coping strategies in their professional life [54,55], again, especially if their levels of stress are low or moderate [36,56]. Future research may investigate coping strategies more deeply and monitor them over time to understand if and how they change in parallel with stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…Research on teachers has shown that these professionals mostly adopt functional (i.e., approach) coping strategies in their vocation, such as acceptance, positive reframing, planning, and active coping, whereas negative strategies are usually avoided (e.g., selfblame, denial, and the use of alcohol or drugs) [54,55]. However, the quality of the coping strategies that they adopt may depend on their levels of stress and burnout.…”
Section: Dealing With Challenging Situationsmentioning
confidence: 99%
“…These subscales can be categorized into three higher-order dimensions: problem-focused coping; emotion-focused coping; and avoidant coping. The methodology is tested and valid, and actively used in modern research (Baghoori et al, 2022;Rajesh et al, 2022;Van Gils, 2022;Weeratunga et al, 2022, Abdul Rahman et al, 2021, Mackay et al, 2021. Internal reliability for subscales ranges from α = 0.57 to α = 0.90 (Carver, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Until such a reckoning, teaching and learning in secondary schools may continue to be affected. Teachers are vital resources who have received less attention than they deserve for their Psychological well-being and yet teachers' stress has been shown to have an impact on their performance all over the world (Rajesh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%